2008
DOI: 10.1590/s1516-89132008000100010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of indomethacin on the pregnant rat

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In this study, SD rats received 4.33, 4.66 and 5.00 mg/kg bwt of IMC on Pd3 and Pd4, demonstrating maternal toxicity. These data are consistent with the findings of a previous study ( Damasceno et al, 2008 ) which demonstrated a decrease in feed intake and body weight from Pd6 to Pd11 in SD rats administered an IMC dose of 8.50 mg/kg bwt. In addition, IMC treatment has an adverse effect on the smooth muscles of the small intestine and a reduced number of embryos were observed.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, SD rats received 4.33, 4.66 and 5.00 mg/kg bwt of IMC on Pd3 and Pd4, demonstrating maternal toxicity. These data are consistent with the findings of a previous study ( Damasceno et al, 2008 ) which demonstrated a decrease in feed intake and body weight from Pd6 to Pd11 in SD rats administered an IMC dose of 8.50 mg/kg bwt. In addition, IMC treatment has an adverse effect on the smooth muscles of the small intestine and a reduced number of embryos were observed.…”
Section: Discussionsupporting
confidence: 93%
“…In another study, Both pre-and post-implantation losses increased significantly at a dose of 10 mg/kg/day ( Shafiq et al, 2004 ). The reproductive health of Wister rats was not affected at lower doses of 0.32, 1, and 1.68 mg/kg bwt twice daily from Pd3 to Pd5 ( Damasceno et al, 2008 , Kennedy, 1977 ). EIS was significantly reduced in all rat groups treated with IMC in the current study.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Abnormal Sperm Percent: The sperm was examined and the normal appearance was distinguished from the distorted by the head or tail or both to calculate the abnormal sperm. The same slide was used that was used to calculate the dead and live sperm, and to determine the abnormal appearance of the sperm, the following equation is calculated: (Deformation% = Abnormal number of sperms / Total number of sperms X 100), (Dale and Edler, 1997), (Damascono et al, 2008).…”
Section: Methodsmentioning
confidence: 99%